2008
DOI: 10.1007/s00011-007-7131-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of lymphocytes in the course of murine zymosan-induced peritonitis

Abstract: Lymphocytes do not have a significant impact on zymosan peritonitis in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 37 publications
1
39
0
Order By: Relevance
“…Recent work by Kolaczkowska et al [13] demonstrated comparable changes between RAG-deficient mice and wild-type mice in vascular permeability and PMN infiltration in the model of zymosan peritonitis. In contrast, work by Rajakaria et al [6] suggested that RAG-deficient mice exhibited an exaggerated peritoneal response to zymosan with increased PMN infiltration accompanied by increased TNF-α and reduced IL-10 levels.…”
Section: Lymphocytesmentioning
confidence: 99%
“…Recent work by Kolaczkowska et al [13] demonstrated comparable changes between RAG-deficient mice and wild-type mice in vascular permeability and PMN infiltration in the model of zymosan peritonitis. In contrast, work by Rajakaria et al [6] suggested that RAG-deficient mice exhibited an exaggerated peritoneal response to zymosan with increased PMN infiltration accompanied by increased TNF-α and reduced IL-10 levels.…”
Section: Lymphocytesmentioning
confidence: 99%
“…The viewpoints on the control of innate immune cells by the adaptive immune system during sepsis remain controversial (14)(15)(16)(17)(18). Research using mouse models of sepsis induced by cecal ligation and puncture (CLP) (19) produced different conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…van Schaik et al (14) showed that T cell-deficient mice exhibit markedly decreased disease severity compared to wild-type mice after E. coli injection and suggested that T cells may stimulate innate immune responses, resulting in enhancement of disease. The research on BALB/c mice and Rag-deficient mice with peritonitis induced by zymosan showed that lymphocytes do not have a significant impact on zymosan peritonitis in mice (16). Kim et al (9) showed that lymphocytes suppress activation of innate immune cells in Rag-1 knockout mice with poly (I: C)-induced SIRS.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown reduced leukocyte recruitment (either PMN or M/) [11][12][13], increased leukocyte recruitment [7] or no difference [6,9,14] in various lymphocyte-deficient animals compared to control mice. It should be noted, however, that previous studies of the inflammatory responses of lymphocyte-deficient strains have not examined the numbers of circulating PMNs or monocytes or, in the case of studies of peritoneal inflammation, the numbers of resident peritoneal cells and this complicates interpretation of the available data [7,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Recent work by Kolaczkowska et al [6] demonstrated comparable changes between RAGdeficient mice and wild-type mice in vascular permeability and PMN infiltration in the model of zymosan peritonitis at the 30 min and 6 h time points, respectively [6]. In contrast, work by Rajakaria et al [7] demonstrated that RAG-deficient mice exhibited an exaggerated peritoneal response to zymosan with increased PMN infiltration evident at 2 and 6 h accompanied by increased TNF-a and reduced IL-10 levels.…”
Section: Introductionmentioning
confidence: 86%